2010
DOI: 10.1523/jneurosci.1603-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Memory Formation in Motor Cortex after Adaptation to Force Field

Abstract: Activity of single neurons in the motor cortex has been shown to change during acquisition of motor skills. We previously reported that the combined activity of cell ensembles in the motor cortex of monkeys (Macaca fascicularis) evolves during adaptation to a novel force field perturbation to encode the direction of compensatory force when reaching to visual targets. We also showed that the population directional signal was altered by the available sensory feedback. Here, we examined whether traces of such act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 44 publications
10
48
1
Order By: Relevance
“…Comparisons of directional tuning and the resulting PDs in the three reference frames indicated that, during learning, neuronal activity was always consistent with the force-vector reference frame (Kalaska et al, 1989) but not with target or hand reference frames (Fig. 6 A, B) in which the PDs seemed to shift with forcefield direction as shown previously (Li et al, 2001;Arce et al, 2010b). When perturbation was removed, we observed apparent PD shifts on the population level in the opposite direction, as found in these previous studies.…”
Section: Neuronal Modulations Reflect the Adapted Motor Plansupporting
confidence: 84%
“…Comparisons of directional tuning and the resulting PDs in the three reference frames indicated that, during learning, neuronal activity was always consistent with the force-vector reference frame (Kalaska et al, 1989) but not with target or hand reference frames (Fig. 6 A, B) in which the PDs seemed to shift with forcefield direction as shown previously (Li et al, 2001;Arce et al, 2010b). When perturbation was removed, we observed apparent PD shifts on the population level in the opposite direction, as found in these previous studies.…”
Section: Neuronal Modulations Reflect the Adapted Motor Plansupporting
confidence: 84%
“…Over a short time-scale, fluctuations in the daily behavioral performance correlated with the proportions of task- modulated MIo and SIo neurons; the more neurons were engaged in the task, the higher the success rates. These rapid fluctuations in the pool size of task-related neurons are consistent with the increased tongue representation occurring within an hour of tongue-task training in humans (Svensson et al, 2006;Arima et al, 2011). We would argue that the nonmonotonic fluctuations in success rate within a session do not signify periods of learning and unlearning but reflect the engagement of a learning process that results in monotonic improvements over days.…”
Section: Learning Effects On Behavior and Neuronal Activitysupporting
confidence: 63%
“…Specifically, the orofacial primary motor cortex (MIo) and somatosensory cortex (SIo) exhibit neuroplasticity related to acquisition of novel oromotor skills, intraoral manipulations, and pain (Murray et al, 1991;Lin et al, 1993;Svensson et al, 2003Svensson et al, , 2006Sessle et al, 2005Sessle et al, , 2007AviviArber et al, 2010AviviArber et al, , 2011Arima et al, 2011). Its dysfunction has been implicated in many orofacial sensorimotor disorders affecting feeding and speech found in stroke and Parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous neurophysiological findings on the role of neurons in motor areas for motor learning also imply that the encoding of opposite-arm kinematics is very likely. Many neurons in the contralateral primary motor cortex (MI) are load sensitive (Evarts, 1968;Kalaska et al, 1989), and this load sensitivity emerges during motor learning (Gandolfo et al, 2000;Li et al, 2001;Arce et al, 2010). The neurons of the supplementary motor area (PadoaSchioppa et al, 2002(PadoaSchioppa et al, , 2004 and the premotor area (Xiao et al, 2006) of the contralateral hemisphere are also involved in the adaptation to novel loads.…”
Section: Encoding Of Opposite-arm Kinematics In the Primitivesmentioning
confidence: 99%